The predation relationship between online medical search and online medical consultation—empirical research based on Baidu platform data - Wang, Yang; Ran, Lingshi; Jiao, Wei; Xia, Yixue; Lan, Yuexin (Frontiers in Public Health, 2024)
This study investigates the mutual influence between online medical search and online medical consultation. By leveraging insights from behavioral big data, we examine the health information needs driving these health information-seeking behaviors. Using actual behavioral data from Chinese internet users on the Baidu platform's "Epidemic Index" from November 26, 2022, to January 25, 2023, we conducted data modeling to ensure the model's reliability. Drawing on the logistic model, we constructed a foundational model to quantify the evolutionary patterns of online medical search and online medical consultation, defining an impact function to measure their mutual influence. We conducted a pattern detection experiment to determine the structure of the impact function with maximum commonality through data fitting, thus constructing a mathematical model to quantify the nonlinear correlation between online medical search and online medical consultation. Numerical analysis revealed a predation mechanism between online medical consultation and online medical search, highlighting the role of health information needs in this dynamic. This study offers a novel practical approach to better meet the public's health information needs. Furthermore, the modeling method used in this research is widely applicable, enabling the construction of models to quantify nonlinear correlations among different behaviors given appropriate quantified data.